Antimicrobial resistance in Mycoplasma genitalium sampled from the British general population. (10th January 2020) - Pitt, Rachel; Unemo, Magnus; Sonnenberg, Pam; Alexander, Sarah; Beddows, Simon; Cole, Michelle Jayne; Clifton, Soazig; Mercer, Catherine H; Johnson, Anne M; Ison, Catherine A; Field, Nigel
Abstract : Background: Mycoplasma genitalium is a common sexually transmitted infection. Treatment guidelines focus on those with symptoms and sexual contacts, generally with regimens including doxycycline and/or azithromycin as first-line and moxifloxacin as second-line treatment. We investigated the prevalence of antimicrobial resistance (AMR)-conferring mutations in M. genitalium among the sexually-active British general population. Methods: The third national survey of sexual attitudes and lifestyles (Natsal-3) is a probability sample survey of 15 162 men and women aged 16–74 years in Britain conducted during 2010–12. Urine test results for M. genitalium were available for 4507 participants aged 16–44 years reporting > 1 lifetime sexual partner. In this study, we sequenced regions of the 23S rRNA and parC genes to detect known genotypic determinants for resistance to macrolides and fluoroquinolones respectively. Results: 94% (66/70) of specimens were re-confirmed as M. genitalium positive, with successful sequencing in 85% (56/66) for 23S rRNA and 92% (61/66) for parC genes. Mutations in 23S rRNA gene (position A2058/A2059) were detected in 16.1% (95%CI: 8.6% to 27.8%) and in parC (encoding ParC D87N/D87Y) in 3.3% (0.9%–11.2%). Macrolide resistance was more likely in participants reporting STI diagnoses (past 5 years) (44.4% (18.9%–73.3%) vs 10.6% (4.6%–22.6%); p=0.029) or sexual health clinic attendance (past year) (43.8% (23.1%–66.8%) vs 5.0% (1.4%–16.5%); p=0.001). All 11 participants with AMR-conferring mutations had attended sexual health clinics (past 5 years), but none reported recent symptoms. Conclusions: This study highlights challenges in M. genitalium management and control. Macrolide resistance was present in one in six specimens from the general population in 2010–2012, but no participants with AMR M. genitalium reported symptoms. Given anticipated increases in diagnostic testing, new strategies including novel antimicrobials, AMR-guided therapy, and surveillance of AMR and treatment failure are recommended.